Volatile constituents and antibacterial activity of essential oils of selected Boesenbergia species / Noor Atiekah Md. Nor - Noor Atiekah , Md. Nor (2018)
Essential oils from the rhizomes and leaves of three wild Boesenbergia species from Sabah, namely Boesenbergia armeniaca Cowley, Boesenbergia stenophylla R. M. Sm., Boesenbergia sp. nova, and two wild species from Peninsular Malaysia, namely Boesenbergia plicata (Ridl.) Holttum var. plicata, and Boesenbergia prainiana (King ex Baker) Schltr: were obtained by hydrodistillation. The volatile constituents and their compositions in the oils were identified by Gas Chromatography-Flame Ionization Detector (GC-FID), Gas Chromatography-Mass Spectrometry (GC-MS) and Kovats index analysis. The analysis revealed the presence of monoterpene hydrocarbons, sesquiterpene hydrocarbons, oxygenated monoterpenes, oxygenated sesquiterpenes, diterpene hydrocarbons and oxygenated diterpenes. Five major compounds were identified: methyl cinnamate (55.42%-83.17%) and nerolidol (22.77%-42-55%) from rhizome and leaf oils of Boesenbergia stenophylla and Boesenbergia armeniaca respectively; γ-maaliene (22.82%) from leaf oil of Boesenbergia sp. nova, isocamphene (28.07%) and (-)-β-pinene (21.33%) from rhizome and leaf oil of Boesenbergia plicata, respectively. The antibacterial activity of essential oils against food-borne pathogens namely, Staphylococcus aureus, Bacillus cereus, Salmonella enteritidis and Escherichia coli, were evaluated by disc diffusion assay and their minimum inhibitory concentration (MIC) values were determined. Almost all the essential oils displayed relatively moderate level of MIC values (2.5 mg/mL) against Gram-positive bacteria (Staphylococcus aureus and Bacillus cereus). However, the most potent essential oil was the leaf oil of Boesenbergia plicata (26.5 mm zone inhibition) against Gram-positive bacteria, Bacillus cereus with MIC value of 1.25 mg/mL. Whereas, all the iv essential oils tested against the Gram-negative bacteria (Salmonella enteritidis and Escherichia coli) exhibited low antibacterial activity with MIC value of 5 mg/mL.